Efficacy of Zhu’s acupuncture techniques to improve muscle strength of motion limbs in stroke patients - Indri Seta Septadina; Erial Bahar (Medicinski glasnik, 2020)
Aim: To investigate the efficacy of Zhu acupuncture in motoric ability improvement of stroke patients. This research is a preliminary study in an effort to test the efficacy of Zhu's acupuncture technique in motor improvement in stroke patients. Methods: This quasi-experimental study, with the pretest and posttest approach without control group design was conducted from June to December 2019 at Holistica Medical Centre Complementary Clinic Palembang, Indonesia. Manual Muscle Testing (MMT) was used before and after the intervention. Zhu’s acupuncture was given five times a week for four weeks. Results: Eight patients (four males and four females), who were in the recovery phase (within a period of recovery less than 1 year) after stroke attack were involved. Seven patients experienced improvements in mild and moderate grades for shoulder joint movement after the intervention. Regarding the elbow joint movement, the majority of patients (seven) experienced mild and moderate improvements. Of the total patients who experienced improvement, the majority had mild grade improvements. Conclusion: Zhu’s acupuncture technique was effective in improving muscle strength of motion limbs on stroke patients.
Keywords: acupuncture therapy; movement; muscle strength; stroke